Influence of the Specific Surface Area of Graphene Nanoplatelets on the Capacity of Lithium-Ion Batteries - Esteve-Adell, Iván; Porcel-Valenzuela, María; Zubizarreta, Leire; Gil-Agustí, Mayte; García-Pellicer, Marta; Quijano-Lopez, Alfredo (Frontiers in Chemistry, 2022)
In order to understand the influence of the morphological properties of graphene materials on the electrochemical performance of electrodes for lithium ion batteries, three different graphene nanoplatelets with increasing specific surface area (NP1: 296 m2 g-1; NP2: 470 m2 g-1 and NP3: 714 m2 g-1) where added in the electrode formulation in different ratios. Higher specific surface area graphene nanoplatelets (NP3) exhibit reversible capacity up to 505 mA h g-1 in the first discharge cycle (29,5% higher than graphite). Although significant irreversible capacity is shown for NP3, still higher reversible capacity is obtained compared to graphite electrode. The presence of micropores in graphene structure we found that benefits the lithiation. C-rate capability tests also shows better performance for the graphene based electrode. In this work we demonstrate that graphene nanoplatelets with high specific surface area (714 m2 g-1) improve the electrochemical performance of Li-ion battery electrodes. The relationship between specific surface area, the presence of defects and porosity are discussed.